Manejo agronómico en el cultivo de maíz amarillo duro híbrido Dekalb 1596 en Truz bajo, CHEPÉN - LA LIBERTAD - Rodríguez Cieza, Alan Denis (2015)
In populous Truz Low, Pacanga, Chepén, La Libertad center whose geographic location is located: 7 14 '30 "south latitude, 79 ° 28' 06" W; at a height of 92 m.s.n.m. ceprovaje collaboration with and support of farmers associated research work was performed: Agronomic management in the cultivation of hybrid hard yellow corn DEKALB 1596, in Chepén - La Libertad. The aim of this study was to describe the agronomic management of maize through surveys in the town center district Pacanga Truz low Chepén province of La Libertad department. For the development of this research was visited different farms of producers of yellow corn associated with plant producers Jequetepeque CEPROVAJE valley, which serve as intermediaries so that farmers can sell their product at a good price, they are currently working with BACKUS which is responsible for purchasing the total production of yellow corn in the area. The results show that farmers truz under Chepén La Libertad mainly perform the following agricultural management in the cultivation of hybrid hard yellow corn 1596 DeKalb: disinfect seed, make picket, board and weed burning the area to plant, plow rainfed, use certified seed, chemical fertilizer use, gravity irrigation, insecticides and fungicides applied, andpicking. No use of agronomic practices: soaking seed, hoeing and herbicide application largely. In addition there are massive presence of tar spot when farmers do not perform the proper agronomic practices, not presenting this in the fields of farmers who perform their proper agronomic work. For problems of diseases that have caused losses from 50% as farmers in the area, to which they have chosen as a control and use of preventive, curative chemicals. According to technical recommendations of advisers pesticide various agricultural enterprises in order to make good agronomic management and adequate control on hard yellow corn cultivation area in the district Truz Under Pacanga region La Libertad Province.